2016
DOI: 10.1007/s11896-016-9214-9
|View full text |Cite
|
Sign up to set email alerts
|

The Mystery Man Can Increase the Reliability of Eyewitness Identifications for Older Adult Witnesses

Abstract: Some groups of eyewitnesses, such as older adults and children, are less likely to correctly reject a target absent (TA) lineup, as compared to younger adults. Previous research reports that using a silhouette in a video lineup called 'the mystery man' could increase correct rejections for TA lineups for child eyewitnesses, without reducing correct identifications for target present (TP) lineups (Havard & Memon, 2013). The current study, using older and younger adults, investigated whether using the mystery ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 41 publications
0
8
1
Order By: Relevance
“…The results of the current study found that the wildcard lineup procedure was no more beneficial for older adults than the simultaneous lineup procedure. These results contradict the only other study to examine the wildcard lineup procedure with older adults (Havard et al, 2016). It should be noted, however, that the eyewitnesses in that study were presented with a video lineup.…”
Section: Identification Accuracycontrasting
confidence: 75%
See 4 more Smart Citations
“…The results of the current study found that the wildcard lineup procedure was no more beneficial for older adults than the simultaneous lineup procedure. These results contradict the only other study to examine the wildcard lineup procedure with older adults (Havard et al, 2016). It should be noted, however, that the eyewitnesses in that study were presented with a video lineup.…”
Section: Identification Accuracycontrasting
confidence: 75%
“…When examining target-present lineups, no differences were found as a function of the lineup procedure; however, when examining target-absent lineups, older adults made significantly more correct rejections when presented with the wildcard lineup compared to the control lineup. There was no influence of the wildcard on the younger adults' identification accuracy in both target-present and target-absent lineups (Havard et al, 2016). The results of this study suggest that a salient rejection option (i.e.…”
Section: Lineup Proceduresmentioning
confidence: 47%
See 3 more Smart Citations